Soluble suppression of tumorigenesis-2 is a strong predictor of all-cause, cardiovascular and infection-related mortality risk in haemodialysis patients with diabetes mellitus - Hammer, Fabian; Genser, Bernd; Dieplinger, Benjamin; Egger, Margot; Müller, Thomas; Drechsler, Christiane; März, Winfried; Störk, Stefan; Wanner, Christoph; Krane, Vera (Clinical kidney journal, 2022)
Soluble suppression of tumorigenesis-2 (sST2) is a strong prognostic biomarker of cardiovascular (CV) disease. End-stage kidney disease (ESKD) patients are at high risk of CV events and infections. Herein we investigated the utility of sST2 to predict all-cause and cause-specific mortality in haemodialysis (HD) patients with diabetes mellitus.sST2 concentrations were measured in plasma samples of 1196 participants of the German Diabetes and Dialysis (4D) study who had type 2 diabetes mellitus and received maintenance HD for ESKD. Hazard ratios (HRs) for prespecified, adjudicated endpoints were determined according to sST2 levels at baseline by multivariate Cox proportional hazards analysis.Participants (mean age 66 years, 54% male) had a median sST2 concentration of 25 ng/mL and were followed up for 4 years. After adjustment for possible confounders, participants with sST2 concentrations in the highest (>32.6 ng/mL) compared with the lowest (<20.1 ng/mL) quartile exhibited a 2-fold higher all-cause mortality risk {[HR 2.06 95% confidence interval (CI) 1.61-2.61]; P < .001}. High sST concentrations (fourth versus first quartile) were strongly associated with the risk of cardiac death [HR 2.29 (95% CI 1.55-3.39); P < .001]. Analysis of individual components of cardiac causes of death showed an increased risk of sudden death [HR 2.24 (95% CI 1.33-3.77); P < .001], death due to myocardial infarction [HR 2.12 (95% CI 0.9-5.0); P = .087] and heart failure [HR 3.34 (95% CI 1.15-9.75); P = .027] in participants with sST2 levels in the highest compared with the lowest quartile. Likewise, participants with the highest sST2 levels had an increased risk of fatal stroke [HR 1.92 (95% CI 1.17-3.14); P = .009] and fatal infections [HR 2.01 (95% CI 1.2-3.37); P = .008]. In contrast to fatal CV events, sST2 was not associated with the risk of non-fatal myocardial infarction [HR 0.68 (95% CI 0.41-1.12); P = .132] or non-fatal stroke [HR 1.28 (95% CI 0.64-2.53); P = .485].In HD patients with diabetes mellitus, high concentrations of sST2 were strongly and independently associated with an increased risk of all-cause mortality, CV mortality and death due to infection but not non-fatal CV events.
Gesehen am 25.09.2023